2015
DOI: 10.2214/ajr.14.13575
|View full text |Cite
|
Sign up to set email alerts
|

18F-FDG PET/CT and Melanoma: Staging, Immune Modulation and Mutation-Targeted Therapy Assessment, and Prognosis

Abstract: FDG PET/CT is useful in staging disease, assessing therapy, and determining prognosis in patients with melanoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
28
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(30 citation statements)
references
References 86 publications
2
28
0
Order By: Relevance
“…The evaluation of residual tumors and metastasis after immune checkpoint blockade therapy is essential; however, it has been reported that 18 F-fluorodeoxyglucose (FDG) PET/CT readings can be confounded by the presence of inflammatory cells, which mimic tumor FDG uptake. 3 Consistently, FDG PET/ CT demonstrated mimic tumors in several lymph nodes in our case (data not shown). Thus, other diagnostic tools for the evaluation of residual tumor are required.…”
supporting
confidence: 87%
See 1 more Smart Citation
“…The evaluation of residual tumors and metastasis after immune checkpoint blockade therapy is essential; however, it has been reported that 18 F-fluorodeoxyglucose (FDG) PET/CT readings can be confounded by the presence of inflammatory cells, which mimic tumor FDG uptake. 3 Consistently, FDG PET/ CT demonstrated mimic tumors in several lymph nodes in our case (data not shown). Thus, other diagnostic tools for the evaluation of residual tumor are required.…”
supporting
confidence: 87%
“…1,2 Previous reports speculated that paracrine factors secreted from dermal fibrosis induce proliferation and differentiation of the overlying epidermis. 3 Herein, we present a case of the rare variant of dermatofibroma and performed the first dermoscopic study of the lesion to identify features that can be a dermoscopic clue to the differential diagnosis between typical dermatofibroma and dermatofibroma with overlying sebaceous hyperplasia.…”
Section: Dermoscopic Features Of Dermatofibroma With Overlying Sebacementioning
confidence: 99%
“…While these tracers are well-studied in cancer, they may be limited by inflammatory responses, infections, and malignant tissues with low FDG avidity 28 . For patients treated with immunotherapies, the infiltration of lymphocytes and reactivation of the immune response will naturally result in some local inflammation, making distinction of response versus progression difficult with these tracers 29 . Hence, these tracers may not be effective for imaging of patient response to immunotherapies and targeting of specific cell surface receptors may provide additional benefit.…”
Section: Discussionmentioning
confidence: 99%
“…The vast majority of other available data on the potential utility of 18 F-FDG-PET after ICPIs are case reports more often describing underlying challenges of monitoring radiologic response in these patients and showing 18 F-FDG-PET features of inflammatory reactions. PET-highlighted autoimmune pancolitis, splenic sarcoidosis-like lesion and exacerbation of sarcoidosis as a potential confounder in the assessment of tumor response in a melanoma patient treated with ipilimumab have all been described[25-27]. Similarly, Koo et al[26] illustrated a series of inflammatory reactions with avid FDG uptake in patients treated with ipilimumab, including those with thyroiditis, hypophysitis, granulomatous inflammation in the lymph nodes and skin, and enterocolitis.…”
Section: Textmentioning
confidence: 99%